Caries experience in Indian children with cleft lip and palate – an observational study from a tertiary care centre - Mukhopadhyay, Santanu; Mukhopadhyay, Prasun (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study aims to assess caries experience in children with cleft lip and palate (CLP). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A total of 127 children (aged 3-12 years) with CLP and 141 non-cleft controls were assessed for dental caries using the decayed-extracted/missing-filled teeth (deft/DMFT) index. Logistic regression analysis was employed to identify factors associated with dental caries. Statistical tests, including t-test, ANOVA, Chi-square, and Fisher’s exact test, were used to analyze differences between cleft and non-cleft populations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In primary teeth, caries prevalence was significantly higher in children with CLP (63.8%) compared to non-cleft controls (40.4%, p<0.001). The deft scores were 3.30 for CLP and 1.63 for non-CLP group (p<0.01). No significant difference was observed in mean DMFT scores (p=0.02). Significant variations in caries prevalence (p=0.01) and mean DMFT values (p=0.001) were noted in permanent dentition among different cleft groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Children with CLP show higher caries prevalence and experience, emphasizing the need for targeted dental care interventions in this population. Logistic regression analysis highlights an age-related increase in caries experience among individuals with CLP.